Using Needs Analysis to Develop Global Education Based ELT Materials in Transactional Speaking Skills - Monica, Monica (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This research focuses in developing global education based ELT materials for transactional speaking skills by using needs analysis. It is aimed to enhance the quality of teaching English at the tertiary level by adapting the students’ needs, the expectations of the lecturers and inputs from graduates to give beneficial contribution towards the students’ future career. This is a development research method by applying IDO’s model, which implements three systematic phases (Input, Development, and Output). The first phase is input phase. It is set up by needs analysis which is carried out by requiring 130 respondents (110 students, 8 lecturers and 12 graduates). Students and graduates are selected randomly while the lecturers are selected by using purposive sampling technique. The data are collected through needs analysis questionnaire and analyzed by using descriptive approach. The second phase, development, attempts to formulate the aim and the objectives based on the information of needs analysis which is used for selecting course contents. In the last phase is output phase. It is administered by compiling the lesson plan and producing the prototype of the global education based ELT materials for speaking skill, specifically transactional speaking skills. The findings of this research have confirmed the importance of using needs analysis as the basis of obtaining information about students’ linguistic and learning needs as well as for developing well-design ELT materials. This contributes to the prototype of an adaptive developed ELT materials comprising one sample of lesson plan and one unit of global education based instructional materials for transactional speaking skills development.